Calculation of the strength of airport paving from the effects of dimensional aircraft - Цихановський, В.К.; Талах, С.М.; Трушківська, Н.Л. (Proceedings of National Aviation University (archive), 2009)
Methodology of define more precisely solution on strength of airdrome strict outercoveres on base numerical realization with help method of finite element are presented. Recommendations to introduce in existence standardized documents of corresponding transitory parameters for determination calculative the bending moments of concrete plate outercoveres with dependent on strength of soil foundation are given. Task of solution real two-layer concrete outercover on strict man-made foundation of platform terminal complex of airport Borispol are solved.